Corporate Social Responsibility (CSR) Practices of NLC India Limited- A Study of Public View Point and their Satisfaction (International Journal of Food and Nutritional Sciences, 2022)
With the advent of globalization, the world has emerged as a small village with investment in business across the world. The new economic policy of India has also changed the scenario of Indian economy which resulted in the investment opportunities for doing business across nations thereby resulted in the growth of corporations using the resources both human and man-made on large scale. This huge utilization of resources lead to the destruction of environment specially in mining and extraction companies and also affects the life of the immediate community living in nearby areas which increased the attention of corporations towards the concept of social responsibilities of business or Corporate Social Responsibilities (CSR). CSR has been widely used by different countries across the world but India became the first ever country with legislated CSR. The government of India has mandated CSR according to the provisions of Companies Act 2013 and the CSR guidelines issued by the Department of Public Enterprises (DPE) and made CSR mandatory for the Public Sector Undertakings with a certain criteria. The present paper mainly aimed to analyze the CSR practices of a public sector enterprise - Neyveli Lignite Corporation India Limited a Navratna Status company in the Tamil Nadu, India. This paper is based on primary data collected through the personal visits in the nearby areas of the corporation under study. The findings of this study revealed that NLC India Limited at a very little extent is doing CSR activities in the sample areas and the authors suggested that there is a dire need of implementation of the CSR practices in these areas under study.